Observer-based sliding mode control for bilateral teleoperation with time-varying delays. (October 2019) - Yang, Hongjiu; Liu, Lei; Wang, Yingjie
Abstract: In this paper, a tracking control scheme is investigated for a bilateral teleoperation system with time-varying delays and dynamic uncertainties. The tracking control scheme is based on an extended state observer (ESO), a time-delay part observer and a continuous terminal sliding mode control (CTSMC) strategy. The dynamic uncertainties are dealt with by the ESO for the bilateral teleoperation system. The time-varying delays with unmeasurable derivatives are estimated by the two time-delay part observers. The CTSMC strategy is used to ensure finite-time convergence for the bilateral teleoperation system without knowing the second derivatives of tracking errors. Finally, experiment results are shown for the bilateral teleoperation system to demonstrate effectiveness of the developed tracking control scheme.